2012
DOI: 10.1371/journal.pone.0048857
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of a Single Session of Transcranial Direct Current Stimulation on Experimentally Induced Pain in Patients with Chronic Low Back Pain – An Exploratory Study

Abstract: Transcranial direct current stimulation (tDCS) has been shown to modulate cortical excitability. A small number of studies suggested that tDCS modulates the response to experimental pain paradigms. No trials have been conducted to evaluate the response of patients already suffering from pain, to an additional experimental pain before and after tDCS. The present study investigated the effect of a single session of anodal, cathodal and sham stimulation (15 mins/1 mA) over the primary motor cortex on the perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…Overall, we found significant improvement of cold and heat pain tolerance following real tDCS, consistent with other studies [59][65]. The large variability in the QST values found in our study, especially for cold pain thresholds, are similar to other reported values [66], [67].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, we found significant improvement of cold and heat pain tolerance following real tDCS, consistent with other studies [59][65]. The large variability in the QST values found in our study, especially for cold pain thresholds, are similar to other reported values [66], [67].…”
Section: Discussionsupporting
confidence: 93%
“…The effect of a-tDCS on neurophysiological outcomes (such as evoked potentials) demonstrated in the present study, were also reproduced in the majority of trials after tDCS (Matsunaga et al, 2004 ; Csifcsak et al, 2009 ; Luedtke et al, 2012 ). Perhaps the psychophysical variables depend on a range of different pathways because evaluation of pain is a more complex process than mere somatosensory processing in evoked potentials.…”
Section: Discussionsupporting
confidence: 77%
“…Other explanations for these results, that challenge our hypothesis, are evidences of previous clinical studies, which demonstrated that the behavioral data did not indicate a pain-reducing effect of anodal stimulation (Grundmann et al, 2011 ; Jürgens et al, 2012 ; Luedtke et al, 2012 ). Interestingly, previous studies on experimental pain using the same stimulation paradigm also showed inconclusive effects of tDCS on psychophysical variables (Grundmann et al, 2011 ; Jürgens et al, 2012 ; Luedtke et al, 2012 ). These inconclusive effect of change on cortical nociceptive processing, as a response to heat pain was also reported in other recent study, which did not found neither cathodal nor anodal tDCS effect over the left M1 (1 mA, 15 min) (Ihle et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 41%
“…tDCS exerted subclinical antinociceptive effects, and these occurred in the predicted direction, but these were neither statistically significant nor within a clinically meaningful range. Interestingly, previous studies on experimental pain using the same stimulation paradigm also showed inconclusive effects on psychophysical variables [24,27,38], whereas neurophysiological outcomes (such as evoked potentials) were altered in the majority of trials after tDCS [5,14,40]. One potential explanation could be that psychophysical variables depend on a range of different pathways because evaluation of pain is a more complex process than mere somatosensory processing in evoked potentials.…”
Section: Discussionmentioning
confidence: 95%